An Optimized Injectable Hydrogel Scaffold Supports Human Dental Pulp Stem Cell Viability and Spreading. (16th May 2016) - Jones, T. D.; Kefi, A.; Sun, S.; Cho, M.; Alapati, S. B.
Abstract : Introduction . HyStem-C ™ is a commercially available injectable hydrogel composed of polyethylene glycol diacrylate (PEGDA), hyaluronan (HA), and gelatin (Gn). These components can be mechanically tuned to enhance cell viability and spreading. Methods . The concentration of PEGDA with an added disulfide bond (PEGSSDA) was varied from 0.5 to 8.0% (w/v) to determine the optimal concentration for injectable clinical application. We evaluated the cell viability of human dental pulp stem cells (hDPSCs) embedded in 2% (w/v) PEGSSDA-HA-Gn hydrogels. Volume ratios of HA : Gn from 100 : 0 to 25 : 75 were varied to encourage hDPSC spreading. Fibronectin (Fn) was added to our model to determine the effect of extracellular matrix protein concentration on hDPSC behavior. Results . Our preliminary data suggests that the hydrogel gelation time decreased as the PEGSSDA cross-linker concentration increased. The PEGSSDA-HA-Gn was biocompatible with hDPSCs, and increased ratios of HA : Gn enhanced cell viability for 14 days. Additionally, cell proliferation with added fibronectin increased significantly over time at concentrations of 1.0 and 10.0  μ g/mL in PEGDA-HA-Gn hydrogels, while cell spreading significantly increased at Fn concentrations of 0.1  μ g/mL. Conclusions . This study demonstrates that PEG-based injectable hydrogels maintain hDPSC viability and facilitate cell spreading, mainly in the presence of extracellular matrix (ECM) proteins.